Evaluation of Ventricular Repolarization Dispersion During Acute Myocardial Ischemia: Spatial and Temporal ECG indices - Arini, Pedro David (2014)
In this work, we studied the evolution of different electrocardiogram (ECG) indices of ventricular repolarization dispersion (VRD) during acute transmural myocardial ischemia in 95 patients undergoing percutaneous coronary intervention (PCI). We studied both temporal indices of VRD (T-VRD), based on the time intervals of the ECG wave, and spatial indices of VRD (S-VRD), based on the eigenvalues of the spatial correlation matrix of the ECG. The T-wave peak-to-end interval ITPE index showed statistically significant differences during left anterior descending artery and right coronary artery (RCA) occlusion for almost the complete time course of the PCI procedure with respect to the control recording. Regarding S-VRD indices, we observed statistically significant increases in the ratio of second to the first eigenvalue IT21, the ratio of the third to the first eigenvalue IT31 and the T-wave residuum ITWR during RCA occlusions. We also found a statistically significant increase in the IT31 during left circumflex artery occlusions. To evaluate the evolution of VRD indices during acute ischemia, we calculated the relative change parameter RI for each index I. Maximal relative changes (RI) during acute ischemia were found for the S-VRD indices IT21, the first eigenvalue Iλ1 and the second eigenvalue Iλ2, with changes 64, 57 and 52 times their baseline range of variation during the control recording, respectively. Also, we found that relative changes with respect to the baseline were higher in patients with T-wave alternans (TWA) than in those without TWA. In conclusion, results suggest that ITPE as well as IT21, IT31 and ITWR are very responsive to dispersion changes induced by ischemia, but with a behavior which very much depends on the occluded artery.